FACTORS INFLUENCING THE ADOPTION OF E-GOVERNMENT SERVICES AMONG BABY BOOMERS AND OLDER ADULTS. (11th November 2018) - Hong, S; Choi, M
Abstract: This study examines the socioeconomic factors associated with the adoption of e-government services among the aging population in South Korea, with a focus on the comparison between baby boomers and the current cohort of older adults. Data came from the 2015 E-Government Service Usage Survey, a nationally representative survey, in South Korea. Analysis was limited to participants born between 1963 and 1955 (baby boomers, N=795) and those born before 1955 (older adults, N=464). Participants were asked whether they were aware of and used e-government services such as searching information, paying taxes, and filing a civil rights complaint on the Internet or mobile devices. Multinomial logistic regression models were estimated to examine the relationships of gender, age, education, employment status, and income with the adoption of e-government services by cohort. Baby boomers reported being aware of and using e-government services twice more than older adults (68.4% and 34.7%, respectively). For both cohorts, being aware of and using e-government services relative to being unaware of e-government services was associated with a higher level of education and being employed. For baby boomers, higher income was associated with being aware of e-government services. The findings suggest that age-divide in e-government service usage would decrease in the future, but older adults with limited education and income would be still at high risk of marginalization in relation to e-government service usage.